The Impact of Social and Cultural Identities on the Development of Social Competence : A Case Study - Satoto, Agus; Mujiyanto, Januarius; Saleh, Mursid; Faridi, Abdurrahman (Journal of Asia TEFL, 2020)
English teachers are required to be able to make appropriate interpersonal and intercultural interactions or communication (Zhang, 2017). They shall be able to show, teach, and guide their students on how to make appropriate intercultural communication and should have great social competence and intercultural interaction skill. The research question of this study is, “How do social and cultural identities impact the development of social competence?”